IMPLEMENTATION OF THE QUANTUM LEARNING MODEL TO IMPROVENATURAL SCIENCE LEARNING OUTCOMES FOR FOURTH-GRADE STUDENTSOF SDN CIPINANG MUARA 07 PG - Isna Putri Azizah; Nadifha Nisrina Putri Ridwan; Yurniwati; Yofita Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Quality learning influences students’ learning outcomes. In accordance with the demands of 21st-century education, teachers need to apply innovative learning models. This paper discusses students’ learning outcomes in natural science learning subjects by applying the Quantum Learning model for fourth-grade students at SDN Cipinang Muara 07 PG. The research design is classroom action research using the Kemmis and Taggart model, which consists of 3 cycles that have stages for each cycle, namely planning, implementation, observation, and reflection. The research data consists of process and students’ learning outcome data. Process data were obtained through observation sheets of teacher and students’ activity and learning outcome data that was obtained through tests. The research results indicate an increase in the completeness of students’ learning outcomes in each cycle. Students who completed Cycle I were only 46% and students who did not complete were 54%. In cycle II, it increased to 64% for students who completed and 36% for students who did not complete. Meanwhile, in cycle III, most of the students achieved 86% and only 14% have not achieved the result. In conclusion, there was an increase in learning outcomes in each cycle so it can be argued that the implementation of the Quantum Learning model in natural science learning subjects on plant parts learning material succeed in improving students’ learning outcomes.